6 - The ’Universal’ in science as a Dilemma for scholarship in Africa - Olajide Oloyede, (Identity, Culture and Politics, 2011)
The dominant of western knowledge in the understanding of the complexion of the social reality in Africa is widely acknowledged. The attempt at a corrective to this perverse dominance has seen the increasing acceptance in the social sciences, in particular sociology, that there is at least two different realms of knowledge to be gained – scientific and non-scientific both of which are generally considered to characterize western knowledge and non-western knowledge respectively and how, to a different extent, we relate ourselves to our world intimately connected to these realms. The idea that there are realms of knowledge somehow poses a problem of the relation of knowledge to relevance where the concern is primarily with the relevance of knowledge gained in the quest for understanding our world for some kind of social action. The problem of knowledge to relevance becomes the problem of the ‘universal’. This paper argues that this is the dilemma for African social science. It steps a back into the history of western thought to point to the enduring nature of the ‘tools’ of understanding that scholars of Africa (Africans and Europeans) use to make sense of the African context as part of the dilemma.